Monoarylamines in the general population – A cross-sectional population-based study including 1004 Bavarian subjects - Kütting, Birgitta; Göen, Thomas; Schwegler, Ursula; Fromme, Hermann; Uter, Wolfgang; Angerer, Jürgen; Drexler, Hans (International journal of hygiene and environmental health, 2009)
The population-based cross-sectional study including 1004 Bavarian volunteers aged 3 up to 84 years (median: 42 years) was aimed to quantify the internal burden of monocyclic arylamines in the general population and to yield reference values. Participants were asked to complete a questionnaire, to give a venous blood sample and a urinary sample. The selected monoarylamines (aniline, o-anisidine, all isomers of toluidine, single and double chlorinated anilines) represent main sources of potential environmental exposure. The venous blood sample was taken to determine the smoking-specific acrylonitrile-adduct N-cyanoethylvaline. Detectable levels of aniline were found in the urine of 93.9% of the participants, whereas 3-chloroaniline was only detected in 16% of the samples. The influence of smoking on the urinary arylamine concentration was weak. Only for o-toluidine, m-toluidine and o-anisidine values were significantly higher in smokers. Therefore, while the 95th percentile based on the total sample ( n=1004) is the best reference value for all other arylamines (i.e. p-toluidine, 3-chloroaniline, 4-chloroaniline, 3,4-dichloroaniline) we suggest separate reference values for smokers and non-smokers for the former three compounds. A statistically significant difference in urinary arylamine concentration between men and women was observed for 3,5-dichloroaniline, o-anisidine and aniline ( p<0.001). Therefore we suggest gender-specific reference values for dichloroaniline and aniline; for o-anisidine we suggest gender- and smoking-specific reference values. The observation of o-toluidine in 178 urinary samples in concentration above the limit of quantification raises concern regarding human carcinogenicity. This study supports the notion of further relevant sources of o-toluidine exposure except smoking and occupation. Compared to other environmental risk factors (e.g. environmental tobacco smoke) the risk of o-toluidine-induced cancer seems to be extremely low for the general population.